Ten years of experience with pediatric neuroendoscopic third ventriculostomy - Features and perioperative complications of 210 cases - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2005)
Obstructive hydrocephalus remains a problem, and improvements in fiberoptic technology have promoted interest in neuroendoscopic ventriculostomy (NTV) as an alternative to standard cerebrospinal fluid shunts. The present study assessed 2 10 pediatric NTVs performed between 1994 and 2004 in patients aged 2 months to 10 years. Five children needed same-session ventriculoperitoneal shunting due to insufficient bypass of the obstruction. The other 205 procedures were technically successful, but 7 patients needed early-postoperative shunting and 10 required late shunting. During NTV 86 (40.1 %) of the patients developed arrhythmia. One patient arrested during balloon dilatation, but normal rhythm returned after deflation and epinephrine/atropine therapy, with no resultant morbidity. Twenty-six (10.2%) patients developed tachycardia (without hypertension) followed by bradycardia, and 6 children (2.8%) developed hypertension. In 1 case (0.5%), a branch of the basilar artery ruptured during fenestration and the hemorrhage was controlled after craniotomy. In 5 cases, mild venous bleeding was controlled by irrigation. The early complications included transient ocular divergence (n = 1), anisocoria (n = 2), and hyponatremia (n = 5). Five children were diagnosed with temporary diabetes insipidus in the late-postoperative period. The neuroendoscopic approach is considered safe for treating hydrocephalus in children, but complications can be severe or lethal and the anesthesiologist must respond accordingly.
Keywords: cerebrospinal fluid shunts; obstructive hydrocephalus; neuroendoscopy; ventriculostomy; ENDOSCOPIC 3RD VENTRICULOSTOMY; INTRACRANIAL-PRESSURE; ANESTHESIA; REMIFENTANIL; BRADYCARDIA; ALFENTANIL